UPAYA MENINGKATKAN SEMANGAT BELAJAR MELALUI STRATEGI REWARD PADA SISWA MTs YAYASAN PENDIDIKAN ISLAM (YASPI) KECAMATAN MEDAN LABUHAN - Muhammad Al-Asyari (Fakultas Agama Islam, 2021)
The purposes of this study were: to find out how the students' enthusiasm for learning was at the Islamic Education Foundation MTs (YASPI) in Medan Labuhan District before and after the reward strategy was applied and to find out the form of the reward strategy carried out by the teacher for the students of the Islamic Education Foundation MTs (YASPI) Medan Labuhan District. The method used in this research is descriptive method. The population studied were all students of class VIII, totaling 104 students. From this population, 36 students were assigned as samples by random sampling. The data collection tools used are questionnaires, interviews, and observations. The data analysis technique uses frequency distribution data analysis according to the relative frequency formula (percentage number). The results showed that the learning enthusiasm of the students of MTs Islamic Education Foundation (YASPI) Medan Labuhan District before the reward strategy was applied was categorized as adequate with an average value of 77.55. The form of reward strategies carried out by teachers for students of MTs Islamic Education Foundation (YASPI) Medan Labuhan District, among others; First, thank you, praise, thumbs up and plus points. The reward is given to students when they finish doing the task. Second, awards. The reward is given to students who get the best grades or students who excel among their friends and the provision of scholarships and other assistance to students who excel. The scholarship is obtained from the school's annual budget plan. The learning enthusiasm of the students of MTs Islamic Education Foundation (YASPI) Medan Labuhan Subdistrict after the reward strategy was applied was categorized as good with an average score of 79.32.